Exploring Research on the Development of Modern Physics Learning Tools: Conceptual Study - Marisda, Dewi Hikmah; Tolla, Ismail; Arsyad, Muhammad (Berkala Ilmiah Pendidikan Fisika, 2024)
This article presents a conceptual study (literature review) of several research results focused on developing modern physics learning tools. The research subject comprises ten articles from national and international journal databases within the last ten years (2014-2024). The results of the conceptual study show that several studies have developed teaching materials for Modern Physics lectures, but they still have limitations. These limitations are that the scope of the modern physics material developed has yet to be efficient for students to use online; the teaching materials developed in the form of applications are quite heavy when opened using a smartphone and require quite a large storage space capacity. The use of multimedia in physics learning in Indonesia is quite rapid, easy to present material, efficient to use, and supported by the latest applications to produce teaching materials that can insert text, images, videos, and interactive quizzes. The conclusion obtained from this conceptual study research is that the development of modern physics learning tools has been proven to improve the quality of learning, and there has yet to be any development of modern physics teaching materials based on interactive multimedia. The results of this conceptual study became one of the bases for developing teaching materials for modern physics based on interactive flipbooks.Implications of research on curriculum development and modern physics improving students' critical thinking skills. This approach is expected to increase students' interest in studying modern physics.